Financial Markets and Electricity Consumption Nexus in Saudi Arabia - Senan, Nabil Ahmed Mareai; Mahmood, Haider; Liaquat, Sehrish (International Journal of Energy Economics and Policy, 2018)
Financial market is growing at faster speed in Saudi Arabia with a policy of economic diversification. This may require the more Electricity Consumption (EC) in turn. This paper has investigated the electricity consumption and Financial Market Development (FMD) nexus incorporating economic growth and urbanization in analyses by using a period 1970-2015 for Saudi Arabia. We have found positive effects of economic growth, urbanization and FMD on the EC in long and short run analyses. Based on results, we recommend the Saudi economy to increase the electricity production capacity through several energy resources especially renewable and clean sources to meet the demand from rising economic growth, urbanization and FMD. Keywords: Financial Market Development; Electricity consumption; Urbanization; Economic Growth JEL Classifications: D53; Q41; P25; O47